ANALYSIS OF INFORMATION TECHNOLOGY INFRASTRUCTURE AT TOMORO COFFEE: MATURITY EVALUATION AND DEVELOPMENT STRATEGY - Naufal; Reva Azzahra Triana; Fenny Purwani (International Journal of Multidisciplinary Reseach, 2026)
Information Technology (IT) infrastructure plays a crucial role in supporting operations and competitiveness of companies in the digital era. This study aims to analyze the implementation of IT infrastructure at TOMORO Coffee, one of the rapidly growing modern coffee chain companies in Indonesia. The analysis was conducted using the 7 Components of IT Infrastructure framework by Laudon and Laudon (2022), which includes computer hardware platforms, computer software platforms, enterprise software applications, data management and storage, networking and telecommunications platforms, internet platforms, as well as consulting and system integration services. The research method employed was descriptive qualitative through direct observation at TOMORO Coffee outlets. The maturity level was measured using the COBIT model and supplemented with SWOT analysis, competitor analysis, and gap analysis. The findings indicate that TOMORO Coffee is at the Managed level (average score of 3.85) with strengths in operational digitalization through the integrated TOMORO Smart POS system. However, significant gaps were identified in AI Analytics, Predictive Reporting, Personalized CRM, and Zero Trust Security. A strategic IT infrastructure development plan for the 2026–2030 period is recommended to enhance the company's competitiveness.